Stiffness and strength of cranioplastic implant systems in comparison to cranial bone. Issue 3 (March 2018) - Persson, Johan; Helgason, Benedikt; Engqvist, Håkan; Ferguson, Stephen J.; Persson, Cecilia
Abstract: Purpose: The aim of this study was to evaluate skull replacement options after decompressive craniectomy by systematically investigating which combination of geometrical properties and material selection would result in a mechanical response comparable in stiffness to that of native skull bone and a strength as high or higher than the same. Materials and methods: The study was conducted using a Finite Element Model of the top part of a human skull. Native skull bone, autografts and commercial implants made of PEEK, solid titanium, two titanium meshes and a titanium-ceramic composite were modeled under a set load to evaluate deformation and maximum stress. Results: The computational result showed a large variation of the strength and effective stiffness of the autografts and implants. The stiffness of native bone varied by a factor of 20 and the strength by a factor of eight. The implants span the entire span of the native skull, both in stiffness and strength. Conclusion: All the investigated implant materials had a potential for having the same effective stiffness as the native skull bone. All the materials also had the potential to be as strong as the native bone. To match inherent properties, the best choice of material and thickness is thus patient specific, depending on the quality of the patient's native bone.